Status of zinc in pulmonary tuberculosis - Hassan Ghulam; Syed Manzoor Kadri; Ahmad Manzoor; Qureshi Waseem; Mohammad Syed Aatif; Ghulam Qadir Khan; Kak Manish (Journal of Infection in Developing Countries)
Background: To study the status of zinc as a micronutrient in pulmonary tuberculosis, in our population, with the aim to see the effectiveness of therapy. Methodology: This prospective study includes 50 patients with pulmonary tuberculosis and 30 subjects as the control group. The patients were placed into three stages (1 to 3) on the basis of chest radiographic findings. Serum zinc levels were estimated before, during, and after completion of antitiberculosis therapy. Results: Statistically significant fall in serum zinc levels was seen with advanced age and disease, and the levels improved after initiation of antituberculosis therapy. Conclusion: Estimation of serum zinc levels is an important tool in diagnosis and monitoring of response to treatment in pulmonary tuberculosis, and even a booster of the immunological mechanisms if instituted during the course of treatment.